Effect of Films Thickness on Structural and Optical Properties of Gold (Au) Thin Films Prepared by DC Magnetron Sputtering - Amer, Moatasim; Ghazai, Alaa Jabbar (Iraqi Journal of Science, 2022)
In this paper, the effect of films thickness on the structural and optical properties of gold (Au) thin films prepared by the DC sputtering method was studied. At three different deposition times, three samples of gold thin films of three different thicknesses (200,400, and 600 nm) were prepared. X-ray diffraction patterns, scanning electron microscopy (SEM), and atomic force microscopy (AFM) images, as well as optical spectroscopy, were used to characterize thin films. The crystalline structure of gold thin films was determined by the XRD pattern which showed to be cubic phase and polycrystalline in nature. The preferred orientation was (111) at 2Ѳ equal 37.4. The effect of deposition time on the morphology of the deposited films was visualized with a scanning electron microscope (SEM) which showed a homogenous surface with nanoparticles with a diameter size of 50-100 nm. Changes in deposition time caused variations in roughness, thickness, and surface quality, as shown by AFM results. UV-Vis reflection spectroscopy was also used to investigate the optical properties of thin films.